Is Host Selection by Mosquitoes Driving Vector Specificity of Parasites? A Review on the Avian Malaria Model - Gutiérrez-López, Rafael; Bourret, Vincent; Loiseau, Claire (Frontiers in Ecology and Evolution, 2020)
Parasites and hosts are in a complex evolutionary arm race where host compatibility represents a key obstacle for successful infections. The degree of parasite specialization on a host varies along a continuum: on one end, extreme specialist parasites may be restricted to a single host species, and on the other, generalist parasites are able to infect a diverse set of hosts. Multiple intrinsic factors associated to the host, such as their immune system and physiological condition, can contribute to the evolution of host specificity of parasites and have been well-studied and documented in vertebrates. In contrast, vector specificity of parasites has been largely overlooked, especially in natural conditions. While a few studies suggested that insect vectors do not play an important role in shaping the parasite community structure since they may feed widely from the bird community, current studies have demonstrated the importance of vector feeding behaviour on transmission dynamics for several vector-borne pathogens. Here, we provide a review on the specialization of avian Plasmodium in vectors, emphasizing the necessity to study simultaneously the three players to further understand how host choice by the vectors might influence the distribution of parasites in the wild. In addition, we suggest specific research directions making use of both empirical data gathered in the field and controlled experiments on vector host‐feeding preferences